2021
DOI: 10.1186/s13046-021-02087-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-triggered changes in stromal compartment drive tumor invasiveness and progression of breast cancer

Abstract: Background Chemotherapy remains a standard treatment option for breast cancer despite its toxic effects to normal tissues. However, the long-lasting effects of chemotherapy on non-malignant cells may influence tumor cell behavior and response to treatment. Here, we have analyzed the effects of doxorubicin (DOX) and paclitaxel (PAC), commonly used chemotherapeutic agents, on the survival and cellular functions of mesenchymal stromal cells (MSC), which comprise an important part of breast tumor m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 54 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…This effect is consistent with data from the NCI-60 cell lines treated with doxorubicin. Although stromal cells can play a critical role in doxorubicin drug treatment response 12 , dose-response curves were superimposable for breast cancer cell lines and TM98 ex vivo slices suggesting that cancer cells rather than stromal cells are responsible for diacetylspermine secretion.…”
Section: Discussionmentioning
confidence: 97%
“…This effect is consistent with data from the NCI-60 cell lines treated with doxorubicin. Although stromal cells can play a critical role in doxorubicin drug treatment response 12 , dose-response curves were superimposable for breast cancer cell lines and TM98 ex vivo slices suggesting that cancer cells rather than stromal cells are responsible for diacetylspermine secretion.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, it has been shown that MSCs isolated from mammary AT (MAT-MSCs) of patients with BC displayed a dysregulated secretory profile and enhanced tumorigenicity compared to MAT-MSCs isolated from healthy donors, suggesting permanent changes induced by cancer cells in local MSCs [ 25 ]. Moreover, it has been reported that MAT-MSCs are largely modified by doxorubicin and paclitaxel, which influence cytokine release and potentiate the ability of MSCs to stimulate BC invasive potential in vivo [ 24 ]. Thus, local MSCs exhibit a pivotal role in BC progression and are extensively affected by external stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, by switching on multiple, but still unclear mechanisms, MSCs may favor tumor growth and progression. However, different studies indicate MSCs as vectors for consolidated and innovative therapies [ 9 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…MSC-CD9 may become an important target for the treatment of BC ( 130 ). Adriamycin and paclitaxel promote the production of the serine enzymes E1, CCL2, IL-6 and IL-8 in MSCs and promote breast cancer cell proliferation and angiogenesis ( 131 ). Adriamycin can also cause MSCs to produce miR-21-5p to lead to chemotherapy resistance.…”
Section: Interaction Between Conventional Treatments and The Tumor Mi...mentioning
confidence: 99%